Sex-related differences in heart failure patients: physiological mechanisms of cardiovascular ageing and evidence-based sex-specific medical therapies - Andra Maria Ciutac; Tiberiu Pana; Dana Dawson; Phyo Kyaw Myint (Therapeutic Advances in Cardiovascular Disease)
This review aims to describe the sex differences in heart failure (HF) patients, with a particular emphasis on the effect of cardiovascular ageing. Additionally, it takes into consideration the sex-related variation in cardiovascular health and physiology and the role ageing plays in HF and its implications in drug therapy. The pharmacokinetics and pharmacodynamics of the common HF medications, classified according to the established sub-types, are summarised with respect to sex-specific documented findings. Despite numerous studies confirming significant differences in HF outcomes according to sex, there are no current guidelines that consider patients’ sex in medical therapy of HF. Moreover, females are significantly under-represented in research trials, as well as under-treated in clinical practice, which hinders our understanding of HF in this demographic. Most of the current knowledge on sex-specific HF therapies is driven by secondary analyses of studies not primarily undertaking sex-specific analyses. Therefore, we propose a multi-faceted approach, including increased awareness among healthcare providers and more inclusive research to create a personalised care plan accounting for sex differences in HF management. Given the highlighted knowledge gaps, it is paramount for new research efforts to account for the different sex phenotypes in HF.